THE EFFECTIVENESS OF BEHAVIORAL COUNSELING WITH TECHNIQUES OF SELF-CONTROL TO INCREASE SELF ACHIEVEMENT 1ST GRADE SMA NEGERI 4 SINGARAJA - Komang Tri Paramitha Anggreni (Department of Guidance and Counseling, FIP, Undiksha, 2018)
The purpose of this research is to know the effectiveness of behavioral counseling with techniques of self-control to improve the Achievement of students of class 1st SMAN 4 Singaraja. Experimental research using Pretest Postest Control Group Design. The study Population is students class 1st SMA Negeri 4 Singaraja which amounted to 349. Sample research amounted to 57 students. Through random sampling techniques, 22 students are placed in groups of experiments which get treatment counseling model of behavioral techniques with self-control and 35 students was the Group's control. The data in this study were analyzed by t-test statistic inferensial using software JASP Version 0.7.5.5 and continued with the d'Cohen to calculate the level of effectiveness. The results showed the existence of a difference in self achievement students experimental group after following treatment with self achievement control group get t = 8.963 with < p < 0.001 p then 0.05. Pengijian Effect Size (ES) through d'cohen also shows the level of effectiveness of behavioral counseling model is high (ES = 2.4). The results prove that counseling with techniques behavioral self-control to effectively enhance self achievement grade 1st SMAN 4 Singaraja.